Pengaruh Kompetensi, Budaya Organisasi, dan Reward System terhadap Kinerja Pejabat Pembuat Komitmen dengan Komitmen Organisasi sebagai Variabel Intervening pada Satuan Kerja Lingkup KPPN Ambon - Purba, Rafles Ricadson; Meutia, Meutia; Pane, Sri Gustina (Syntax Literate, 2025)
This study aims to analyze the influence of competence, organizational culture, and reward system on the performance of commitment-making officials (PPK) in the KPPN Ambon environment, with organizational commitment as a mediating variable. The research employs a quantitative approach with data analysis using structural equation modeling (SEM) via SmartPLS4 software. The results indicate that competence and reward systems significantly and positively affect PPK performance, while organizational culture does not have a significant impact. Furthermore, organizational commitment mediates the relationship between competence and the reward system with PPK performance. These findings highlight the importance of enhancing competence and implementing an effective reward system to improve the performance of commitment-making officials in the KPPN Ambon work unit.